Analysis of Factors Affecting Stunting in Toddlers in the Work Area of the Puskesmas Grogol Selatan Village - Putri, Deva Syaharani; Suraya, Izza (Formosa Journal of Sustainable Research, 2024)
Stunting is a chronic malnutrition that causes children under the age of five to be shorter than their peers. Despite its low prevalence, stunting remains a problem that requires further attention and handling. This study aims to determine the factors associated with stunting in toddlers at the Grogol Selatan Village Health Center in 2024. The research design is case control. The case population in this study were toddlers in the Grogol Selatan Urban Health Center Working Area who were stunted while the control population were toddlers who were not stunted. With the total sampling technique, all 27 respondents were selected as cases. While 27 respondents were selected with fixed disease sampling technique as controls. Data were collected by researchers through interviews using a questionnaire. Data analysis was conducted using the Chi-Square test. The results showed a significant relationship between exclusive breastfeeding history (0.014), eating patterns (0.028), maternal nutrition knowledge (0.029), and environmental sanitation (0.026) with the incidence of stunting. Based on the results of this study, education to mothers about stunting prevention is needed